Literature Review: Hubungan Perilaku Higiene Kulit Wajah dengan Akne Vulgaris Pada Wajah - Sitohang, Meyustina Noviantika; Teresa, Astrid; Nawan (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Acne vulgaris (AV) is a common disease of the skin, especially the face in the community. The cause of AV is multifactor, it is said that the hygiene of facial skin is important because unclean skin is one of the triggers for acne vulgaris, because the skin is the entry point for various kinds of microorganisms such as microorganisms that trigger acne vulgaris. Knowing the relationship between facial skin hygiene behavior and acne vulgaris on the face based on scientific evidence. The research used a systematic review approach, analyzed in a structured and planned manner with journal searches using an electronic database (NCBI, Wiley Online Library, Google Schoolar, Europe PMC, Portal Garuda, Research Gate, and DOAJ), use keyword are acne vulgaris, face washing, face washing frequency, face cleanser, face hygiene and face-moisturizer, then screening using inclusion and exclusion criteria and a quality assessment of data (Quality Assessment) according to the criteria. There were 21 journals with findings that stated facial skin hygiene behavior related to Acne Vulgaris were 16 journals and unrelated journal reviews were 5 journals, which were influenced by several confounding factors. There is a relationship between facial skin hygiene behavior and acne vulgaris on the face based on scientific evidence.